Multi-layer heat insulation system for frame construction buildings - Pásztory Zoltán (ENERGY AND BUILDINGS, 2011)
One of the most important research areas today is in energy-efficient technologies such as heat insulation in buildings. In this research, insulation panels with multilayer, low-emissivity aluminum-polyethylene sheets were prepared and investigated. The results of the study showed that surface emissivity and convection currents have important influence on heat flow. The aluminum-polyethylene sheets were effective in reflecting heat and reducing heat transfer by radiation. They also divided the air space in the insulation system, resulting in the reduction of convection currents and convection heat transfer. The heat insulation system was built without micro heat bridges. Consequently, heat conduction was not increased by micro heat bridges resulting in lower effective thermal conductivity than the commonly used insulation materials. The connection between heat resistance and the number of sheets was not linear. The first inserted sheet had the highest effect and each additional sheet had less influence on heat resistance. © 2010 Elsevier B.V. All rights reserved.